Valorization of Water-Based Drill Cuttings through the Bio-Carbonation Approach. (6th May 2022) - Tang, Guowang; Huang, Feng; Wang, Guihe; Song, Zhengyang; Jia, Cangqin; Yu, Peizhi; Sun, Yongshuai
Abstract : This study proposed a novel bio-carbonation method to recycle water-based drill cutting (WDC) to prepare samples, which contains reactive magnesia (MgO) cement (RMC), ground granulated blast furnace slag (GGBS), and fly ash (FA), with the adoption of microbially induced carbonate precipitation (MICP). Through the investigation of some parameters (i.e., GGBS content, FA content, and curing time), the microstructures and strength development of bio-carbonated RMC-based WDC samples were evaluated. The preliminary results revealed that bio-carbonated RMC-based WDC samples outperformed the control group (i.e., without bio-carbonation) in terms of the 28-day strength (i.e., 9.8 MPa versus 4.4 MPa), which can be assigned to formation of the carbonates, that is, hydrated magnesium carbonates (HMCs). Further, in addition to the identification of HMCs, the microstructural analysis also revealed a continuous carbonate network due to the presence of HMCs, which accounts for the strength boost of samples.